2015
DOI: 10.2320/matertrans.mf201407
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Hydrogen Generation from Ammonia Borane on Skeletal Cu Catalysts Prepared from Cu-Ti Amorphous Alloys

Abstract: The catalytic performances of skeletal Cu prepared from Cu-Ti amorphous alloy heated at various temperatures were tested for the hydrogen generation from ammonia borane. The catalytic activity per surface area decreased with increasing heating temperatures of Cu-Ti amorphous alloy. The thermal treatment of Cu-Ti amorphous alloy leads to the high surface area of skeletal Cu. A skeletal Cu catalyst prepared from heated Cu-Ti amorphous alloy at 300°C which is a moderate temperature somewhat lower than crystalliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Recently, we reported that the heating amorphous alloys at moderate temperatures led to enhancement of the catalytic activity of the skeletal metal catalysts . It was found that the atomic arrangement of precursor alloy significantly affects the catalytic properties.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we reported that the heating amorphous alloys at moderate temperatures led to enhancement of the catalytic activity of the skeletal metal catalysts . It was found that the atomic arrangement of precursor alloy significantly affects the catalytic properties.…”
Section: Resultsmentioning
confidence: 99%
“…There has been al ot of research into catalysts for hydrogen generation,a sh ydrogen is an ideal environmentally friendly energy source forf uel cells. The hydrogencontaining compounds formic acid, hydrazine, and ammonia borane are promisingc andidates for the storagea nd transport of hydrogen, [29][30][31][32][33][34][35][36][37] especially,a mmonia borane, which is as olid at RT and has ah igh hydrogen content (19.6 wt %).Three mole equivalents of hydrogen gas is formed upon the decomposition of ammonia borane [Eq. (1)].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our precedent works have demonstrated that skeletal Cu catalysts prepared from Cu-Ti amorphous alloys exhibited higher catalytic activities than mother alloys and those prepared from the corresponding crystalline alloys. It is expected that coating of MOFs on skeletal Cu having a high surface area can afford a catalytically active MOFCu composite material with enhanced catalytic activity of Cu owing to the excellent hydrogen adsorption ability of MOFs.In this study, densely packed MOF crystals on skeletal Cu, which was prepared from Cu-Ti amorphous alloy, 23,24 were fabricated. For the fabrication of, the dissolution rate of Cu ions was controlled by varying the kind of solvent.…”
mentioning
confidence: 99%
“…In this study, densely packed MOF crystals on skeletal Cu, which was prepared from Cu-Ti amorphous alloy, 23,24 were fabricated. For the fabrication of, the dissolution rate of Cu ions was controlled by varying the kind of solvent.…”
mentioning
confidence: 99%